Evaluation of genetic and physiological parameters associated with meat tenderness in South African feedlot cattle - Webb, E.C. (Edward Cottington) (University of Pretoria, 2013)
Dissertation (MSc(Agric) (Animal Science))--University of Pretoria, 2008.